Studying the effect of changes occurring in a thermo-electrochemical cell using an electrogel and different types of Cathode metal - جوخدار, ميلاد (Latakia University Journal -Engineering Sciences Series, 2024)
In this research, several types of thermo-electrochemical cell were studied,which utilize copper as the anode and various metals as the cathode (zinc, aluminum, chromium)in the form of thin sheets with dimensions of (50ˣ30ˣ1) mm, and using a gel electrolyte (electrogel) of sodium alginate with different concentrations (4%, 4.8%, 5.4%, 6.4%, 7.2%, 8%).A study was conducted of the effect of thevalue of the temperature difference between the electrodesandthe difference of the electrolyte concentration on the value of the open circuit voltage of the cell and on the value of the Seebeck coefficient of the cell .The results showed that the open circuit voltage increases with increasing the temperature difference between the two electrodes ∆T for all studied cells. So that the highest cell voltage (690 mV) was obtained when using copper-zinc electrodes and a concentration of 8% for the gel electrolyte, with a temperature difference betweenthe two electrodes (∆T= ). The best value of Seebeck’s coefficient ( =6.02 mv/k ) was also obtained with the same copper-zinc electrodes and a concentration (6.4%) of the gel electrolyte at a temperature difference between the electrodes of (∆T= ).